STRATEGI PEMBELAJARAN DOSEN DALAM MENGEMBANGKAN KEMAMPUAN CRITICAL THINKING MAHASISWA PASCASARJANA PRODI PAI IAIN CURUP - Ririn Eka Monicha; Sutarto Sutarto; Deri Wanto (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2022)
Developing students' critical thinking is very important for every lecturer, especially in postgraduates. Each lecturer has a different strategy in building critical thinking for students in the PAI IAIN Curup postgraduate study program. This study aims to reveal in depth the learning strategies of lecturers in developing critical thinking skills of postgraduate students of PAI IAIN Curup study programs in identifying, analyzing, and evaluating problems in the learning process. This study uses a qualitative research approach. The informants of this research were lecturers who taught at the PAI Postgraduate Study Program of IAIN Curup which consisted of 12 lecturers. The data collection techniques used observation, interviews and documentation techniques. The results showed that in general the lecturer's learning strategies in developing students' critical thinking skills in the aspects of identifying, analyzing, and evaluating problems had the same methods, models and approaches, namely using lecture methods, question and answer, discussions, group assignments, collaborative projects, and inquiries. While the models used are cooperative learning, project based learning, problem based learning, accelerated learning, quantum learning, research-based learning and using an andragogic and student center approach. However, it was also found that the application of the three methods, models, and approaches had different emphases on the aspects of identifying, analyzing, and evaluating problems. So that the selection or application is carried out in the learning process by using methods, approaches, and models that are in accordance with the material or discussion discussed in the lecture process.